Antibacterial activity of the cationic biocide 1-dodecylpyridinium tetrafluoroborate against multidrug-resistant strain of Acinetobacter baumannii - Rogalsky, S.P.; Godyna, D.M.; Semeniuta, I.V.; Tarasyuk, O.P.; Metelytsia, L.O. (Problems of Environmental Biotechnology, 2023)
Hydrophobic cationic biocide 1-dodecylpyridinium tetrafluoroborate (PyrC12-BF4) has been synthesized. The antibacterial activity of cationic biocide against antibiotic-resistant strains-isolates of Acinetobacter baumannii has been established. According to results of molecular docking, the inhibition of the active site FabG may be one of the possible mechanisms of anti-A. baumannii activity of the PyrC12-BF4.